Pengaruh Religiusitas dan Pengetahuan dalam Niat Pembelian Kosmetik Halal: Studi Pada Mahasiswa di Kabupaten Magelang - Ahmad Fuad Hasyim HS; Purwanto Purwanto; Achmad Labib; Mar’atus Sholikhah (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2020)
Abstract- Halal industry has excellent potential to be developed in Indonesia. This potential can be seen from the participation of Muslim populations in Indonesia. Despite having the largest Muslim community in Indonesia, it still lags in the halal industry's development, including in the halal cosmetics sector. This study was conducted to find out how religiosity and students' knowledge in influencing the intention to buy halal Cosmetics. This study involved 150 meetings domiciled in the district of Magelang. The data analysis used is SEM-PLS analysis using SmartPLS. This study proves that religiosity and knowledge have a significant effect on the purchase intention of halal cosmetics.